Pengaruh Latihan Fisik Terhadap Peningkatan Kadar PGC 1 Alpha Pada Otak Mencit Jantan - Renni Hidayati Zein (LPPM Universitas Abdurrab, 2021)
ABSTRACTBacground: The brain is an organ that is susceptible to degenerative processes. When the brain begins to age, there will be a decrease in brain function which is at risk of decreased cognitive function. Aerobic physical exercise can cause oxidative stress by increasing the formation of ROS from aerobic metabolism of muscle cells during physical exercise and cellular stress caused by ROS can trigger cell repair reactions. ROS is a very reactive oxygen-derived free radical, an important generator in the production of ROS is mitochondria, one of which is PGC-1Î±. Purpose: This study aims to measure levels of PGC-1Î± protein in male mice given exercise. Research Method male mice were divided into 2 groups consisting of 6 mice in the control group, 6 mice in the Exercise group with a total of 12 male mice, each 6 weeks old. This research was conducted for 8 weeks using ELISA laboratory techniques to analyze the PGC-1Î± protein. Result: : This study showed that there was an increase in the levels of PGC-1Î± in the brains of male mice after laboratory examination and then continued with statistical tests, the highest value of PGC-1Î± levels in the brains of male mice in the aerobic exercise group was obtained. Conclusion: The administration of aerobic exercise to male mice for 8 weeks had an effect on PGC-1Î± levels in the brains of male mice.